2002
DOI: 10.1074/jbc.m207552200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Nucleocytoplasmic Shuttling of β-Arrestins

Abstract: ␤-arrestins (␤arrs) are two highly homologous proteins that uncouple G protein-coupled receptors from their cognate G proteins, serve as adaptor molecules linking G protein-coupled receptors to clathrin-coat components (AP-2 complex and clathrin), and act as scaffolding proteins for ERK1/2 and JNK3 cascades. A striking difference between the two ␤arrs (␤arr1 and ␤arr2) is that ␤arr1 is evenly distributed throughout the cell, whereas ␤arr2 shows an apparent cytoplasmic localization at steady state. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(106 citation statements)
references
References 41 publications
7
99
0
Order By: Relevance
“…Further experiments to examine the involvement of β-arrestin in this pathway and the identification of the relevant PKB targets are required. At this point, it is still unclear if the nuclear localized receptors interact with β-arrestin or GRKs although both are present in the nucleus [36,37]. Pim-1, a protein kinase downstream of PKB, may also be involved as it plays a pivotal role in the inhibition of both apoptosis and hypertrophy in cardiomyocytes, and its expression affects both JNK and ERK pathways [38].…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments to examine the involvement of β-arrestin in this pathway and the identification of the relevant PKB targets are required. At this point, it is still unclear if the nuclear localized receptors interact with β-arrestin or GRKs although both are present in the nucleus [36,37]. Pim-1, a protein kinase downstream of PKB, may also be involved as it plays a pivotal role in the inhibition of both apoptosis and hypertrophy in cardiomyocytes, and its expression affects both JNK and ERK pathways [38].…”
Section: Discussionmentioning
confidence: 99%
“…Arr3 is known to be distributed in the cytoplasm and associated to plasma and endosomal membranes. Arr3 is predominantly found out of the nucleus due to the presence of its two-leucine nuclear export signal (45). However, Neuhaus et al (46) reported Arr3 to be localized in the nucleus of HEK293 cells and mature spermatozoa.…”
Section: Pgds (Data Not Shown) Strong Growth Was Also Observed On Trpmentioning
confidence: 99%
“…For example, ␤-arr2 (not ␤-arr1) redistributes the prooncogenic ubiquitin ligase Mdm2 (9) and the JNK3 kinase (10) from the nucleus to the cytoplasm. This property depends on the presence of a leucine-rich nuclear export signal in the C terminus of ␤-arr2, which mediates the nuclear export of ␤-arr2 by leptomycin B-sensitive exportins (11). More recently, it has been reported that, despite the fact that ␤-arr1 does not shuttle between the nucleus and the cytoplasm like ␤-arr2, it can accumulate in the nucleus in response to receptor activation and interact with specific promoters.…”
mentioning
confidence: 99%
“…In particular, delocalization of nuclear proteins, such as Mdm2, via the permanent nucleocytoplasmic shuttling of ␤-arr2, may occur even in the absence of receptor activation (9,11) and might thus involve ␤-arr2 oligomers. This hypothesis was investigated here.…”
mentioning
confidence: 99%